2022
DOI: 10.1002/smi.3179
|View full text |Cite
|
Sign up to set email alerts
|

Examining socioeconomic disparities in changes in adolescent mental health before and during different phases of the coronavirus disease 2019 pandemic

Abstract: This study examined socioeconomic disparities in changes in adolescent mental health between fall 2019 (pre‐COVID‐19), spring 2020 (initial coronavirus disease 2019 (COVID‐19) phase), and fall 2020 (prevailing COVID‐19 phase). Using data from 1429 adolescents ( M age = 17.9) from tertiary vocational schools in the Netherlands with n = 386 participating in all three waves, linear and latent basis growth curve models were assessed and multigroup analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 87 publications
0
9
1
Order By: Relevance
“…The study coincided with the Covid-19 pandemic, which began during data collection. There is emerging international evidence from systematic reviews that lower SES adolescents experienced more negative consequences from the pandemic (Collin-Vézina et al, 2022;Kauhanen et al, 2022), analysis of the sample used for the current study suggests that the impact of the pandemic on adolescent mental health may not have varied strongly by family SES (Stevens et al, 2022).…”
Section: The Current Studymentioning
confidence: 87%
See 1 more Smart Citation
“…The study coincided with the Covid-19 pandemic, which began during data collection. There is emerging international evidence from systematic reviews that lower SES adolescents experienced more negative consequences from the pandemic (Collin-Vézina et al, 2022;Kauhanen et al, 2022), analysis of the sample used for the current study suggests that the impact of the pandemic on adolescent mental health may not have varied strongly by family SES (Stevens et al, 2022).…”
Section: The Current Studymentioning
confidence: 87%
“…Seventh, the study coincided with the Covid-19 pandemic, which began between T1 and T2. However, there is evidence that mental health effects of the pandemic were experienced by our entire sample, regardless of SES (Stevens et al, 2022); so, at this post-pandemic stage it remains unclear whether the pandemic influenced the generalizability of the findings.…”
Section: Strengths and Limitationsmentioning
confidence: 90%
“…However, these previous findings may not fully explain why, unlike mood, life satisfaction did not change during the pandemic. Like vigor, it could be that life satisfaction was more susceptible to change in the beginning of the pandemic as compared to later stages (Stevens et al., 2022). Unfortunately, in the present study life satisfaction was not assessed at the first time point.…”
Section: Discussionmentioning
confidence: 99%
“…Many prior studies showed that adolescents with low family income or low socioeconomic status were disproportionally hit by the pandemic (Creswell et al., 2021; Li et al., 2021; O'Connor et al., 2021; Shanahan et al., 2020), but there are also a few studies with mixed results. For example, Stevens and colleagues (2022) showed that during the pandemic (between 2019 and fall 2020) adolescent life satisfaction decreased linearly, but these patterns (i.e., slopes) did not differ between the low or high socioeconomic groups. Another study reported that greater pandemic related economic concerns were associated with declines in anxiety and depression levels over time among some children and adolescents (Cost et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Still, distinctive studies on children with pre‐pandemic risks are scarce to date and limited in their study approaches and age groups (e.g., Adegboye et al., 2021; Stevens et al., 2022; Vallejo‐Slocker et al., 2020). In particular, the distinctive studies on younger children exclusively analyzed parent survey data on child socio‐emotional distress.…”
Section: Introductionmentioning
confidence: 99%